Peran Guru dalam Kegiatan Promosi Kesehatan Pencegahan Obesitas pada Siswa Sekolah Dasar - Nugraheni, Hermien; Prayoga, Aryadiva N; Aida, Wanda Nur (Jurnal Promosi Kesehatan Indonesia, 2019)
Background: Primary school-aged children are at risk of having health problems. One of the health problems that can cause disruption of growth and development is obesity. School is one of the parties who play an important role in providing health education for children which aims to improve healthy living habits of children. The role of school primarily teacher was very important to prevent children obesity. The purpose of this study was to identify the role of teachers in health promotion activities in elementary schools for prevent obesity Method: This study was conducted using descriptive analytical design with cross sectional approach, complemented with qualitative data. The population in this study were teachers in elementary schools who appointed as health school teachers in the working area of Kedungmundu Health Center, Semarang City. Sample of this study was selected purposively by the criteria of active and inactive school health programs. The total sample was 14 teachers for each group, therefore totally 28 teachers involved in this study. Data was collected using face to face interview with trained enumerator and participants signed informed consent before interviewed.   Results: level of Knowledge and attitudes of teachers about health promotion schools for preventing student’s obesity were higher between active and non-active school health program. Teacher's age and education were significantly associated with active school programs with p value 0.039 and 0.040 respectively. Teachers from active school health programs were younger (<30 years old) and have higher education (bachelor) than those who are not active school. Teachers from active school health programs are more initiative to run activities which support nutritional behavior such as provision healthy canteens and physical activities outside the class course rather than only waiting for activities from the health center.